ATRIBUTOS DE QUALIDADE DOS SERVIÇOS PRESTADOS POR UMA IES E OS FATORES QUE IMPACTAM NA SATISFAÇÃO DOS ALUNOS DO CURSO DE GRADUAÇÃO EM ADMINISTRAÇÃO - Gabriel Sperandio Milan (Universidade Federal de Santa Catarina, 2014)
This paper presents a study a bout how to identify the attributes and services quality dimensions (factors), provided by a Higher Education Institution (HEI) that impact in the students of the Administration course’ satisfaction. The operationalization of the research was carried out i nitially by means an qualitative study with exploratory character, with application of seventeen individual interviews, using a semi - structured approach. A set of questions was applied. The interviews were analyzed using content analysis and ended up gener ating attributes (items or observable variables) that can be considered intrinsic to the services quality provided by a HEI. Based on attributes identified in the qualitative research, a structured questionnaire was applied for the students of the Administ ration course and resulted in 346 valid cases. Through factor analysis, the attributes identified were grouped into six analytical dimensions or factors: faculty and curriculum, image and reputation of the HEI, value, cleanliness of facilities, student ser vices and safety. Moreover, by means of multiple linear regression it was possible to explain 52% of the overall student satisfaction according to four factors.